Clinical Practice Guidelines for the Medical Management of Nonhospitalized Ulcerative Colitis: The Patient Perspective - A Hillary Steinhart; Aida Fernandes (Canadian Journal of Gastroenterology and Hepatology)
A series of clinical practice guidelines were recently developed by the Canadian Association of Gastroenterology (CAG) to provide clinicians with recommendations for the medical management of nonhospitalized ulcerative colitis (UC) patients. These guidelines were developed, reviewed and agreed on by expert clinicians and methodologists. Following the finalization of the guidelines, a group of patients with UC as well as several inflammatory bowel disease clinicians, were brought together for a half-day workshop to provide feedback from the patient perspective. At the workshop, the guideline development process was described and the guidelines were reviewed to ensure comprehension. Patients then had the opportunity to provide their insight to the relevance of the guideline development process and the content of the guidelines as it related to their personal experiences with UC. The patient group believed that, although the new guidelines will be a tremendous resource for the health care provider community, a more ‘lay-friendly’ version would better facilitate dialogue between patients and their health care practitioners. The importance of the patient/physician relationship is paramount when making decisions regarding treatment plans, in which patient preferences play a key role in determining the most appropriate therapy and dosing regimen, which, in turn, impact the likelihood of adherence to the treatment plan. It was also believed that quality of life issues were not fully addressed in the guidelines. Much could be learned from shared experiences and coping strategies that would empower patients to take charge of their health and become equal partners with their care providers.